Timing mismatch calibration circuit for high-speed time-interleaved ADC - Seow, Yue Han (2019)
Time-Interleaved Analog-to-Digital Converter (TIADC) is a technique used to achieve a higher conversion speed of analog input signal to a digital output signal. Despite having an excellent operating frequency, this technique suffers from timing mismatch problem of the multiple channels of Analog-to-Digital converters (ADCs) used. This timing mismatch happens when each and every ADC in this system suffers a small delay in capturing the data from the input signal.